Cooperative Learning Model with Role Playing Type Assisted by Hand Puppet Media Improves Elementary School Students Speaking Skills - Bagialih, I Gusti Agung Sitha Pradina Putri; Kristiantari, Maria Goreti Rini (International Journal of Language and Literature, 2024)
Speaking skills are important communication skills for students, but many elementary school students have difficulty developing them. Low speaking skills in students are caused by internal factors such as lack of self-confidence and low motivation, as well as external factors such as less interactive teaching methods and an unsupportive environment. Therefore, this study aims to analyze the effect of the cooperative learning model of the role-playing type assisted by hand puppet media on students' speaking skills. This study uses a quantitative approach with a quasi-experimental design of the non-equivalent post-test-only control group design. The study population was 157 students. The sample was selected using Cluster Random Sampling, totaling 29 students. Data collection was carried out using a speaking skills test carried out after treatment, and the instrument used was a speaking assessment rubric. Data were analyzed using inferential statistical tests with independent sample t-tests to determine the differences in speaking skills between the experimental and control groups. The results showed that there was a significant increase in speaking skills in the experimental group. This study concludes that the cooperative learning model of the role-playing type assisted by hand puppet media can improve students' speaking skills. The implications of this study indicate the importance of using more interactive methods in Indonesian language learning to support the development of students' speaking skills.